Implementación de un plan de continuidad de negocio para el área financiera-tributaria a una empresa industrial dedicada a la producción, comercialización y exportación de madera de balsa para el año 2008 en la ciudad de Guayaquil - Tacury, K. (2009)
This work relates to our thesis, it contains information obtained from an industrial undertaking engaged in the production, marketing and export of balsa wood; the first chapter provides the terminology used in this work, which includes tax and terms of reference in terms of subject matter; the second chapter is the description of the company, its mission, vision, objectives, general organization, etc.., the third and most extensive chapter covering the Business Continuity Plan as a first step is to conduct an Impact Analysis Business, which will identify the main process of the company through a matrix of estimated financial and operational impacts that the company may suffer in the event that one will materialize disaster and identified the time and recovery point objective; IT resources and non-IT to be used depending on the magnitude of the disaster, as a second step will describe the financial-tax department , an assessment of profiles of staff in the area, the next step is to conduct a risk analysis and threats which will be summarized by a matrix, identify alternative solutions to follow, provide information on the financial impact that the company has had since the start of legal proceedings with SRI, through an analysis Cost-benefit evaluation will seek alternative solutions that are convenient for the company and finally give the respective findings and recommendations to avoid past situations will recur.